2015
DOI: 10.1111/mmi.12991
|View full text |Cite
|
Sign up to set email alerts
|

DdrO is an essential protein that regulates the radiation desiccation response and the apoptotic‐like cell death in the radioresistant Deinococcus radiodurans bacterium

Abstract: Deinococcus radiodurans is known for its extreme radioresistance. Comparative genomics identified a radiation-desiccation response (RDR) regulon comprising genes that are highly induced after DNA damage and containing a conserved motif (RDRM) upstream of their coding region. We demonstrated that the RDRM sequence is involved in cis-regulation of the RDR gene ddrB in vivo. Using a transposon mutagenesis approach, we showed that, in addition to ddrO encoding a predicted RDR repressor and irrE encoding a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 45 publications
(81 reference statements)
4
85
1
Order By: Relevance
“…While the IrrE‐mediated cleavage of DdrO was shown in solution after mixing the purified proteins and when coexpressed in Escherichia coli , the in vivo IrrE‐dependent DdrO cleavage in Deinococcus was observed only after exposure to radiation, in agreement with the radiation‐induced derepression of the RDR regulon. More recently, essentially the same conclusion for the role of IrrE in DdrO cleavage and gene induction was reached in two independent studies on D. radiodurans (Devigne et al., ; Wang et al., ). Additional results have been claimed for IrrE of D. radiodurans , namely that it binds, like DdrO, to the promoter regions of RDR genes (Lu, Chen, Xu, Shah, & Hua, ; Wang et al., ), although other studies indicated that IrrE does not bind DNA (Ohba, Satoh, Yanagisawa, & Narumi, ; Vujicic‐Zagar et al., ), and that the protease activity of apo‐IrrE could be restored by manganese but, remarkably, not by zinc ions (Wang et al., ).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…While the IrrE‐mediated cleavage of DdrO was shown in solution after mixing the purified proteins and when coexpressed in Escherichia coli , the in vivo IrrE‐dependent DdrO cleavage in Deinococcus was observed only after exposure to radiation, in agreement with the radiation‐induced derepression of the RDR regulon. More recently, essentially the same conclusion for the role of IrrE in DdrO cleavage and gene induction was reached in two independent studies on D. radiodurans (Devigne et al., ; Wang et al., ). Additional results have been claimed for IrrE of D. radiodurans , namely that it binds, like DdrO, to the promoter regions of RDR genes (Lu, Chen, Xu, Shah, & Hua, ; Wang et al., ), although other studies indicated that IrrE does not bind DNA (Ohba, Satoh, Yanagisawa, & Narumi, ; Vujicic‐Zagar et al., ), and that the protease activity of apo‐IrrE could be restored by manganese but, remarkably, not by zinc ions (Wang et al., ).…”
Section: Introductionsupporting
confidence: 59%
“…Indeed, overexpression of IrrE and DdrO in E. coli showed cleavage of DdrO without applying a stress condition (Ludanyi et al., ). Moreover, a transposon insertion upstream of irrE in D. radiodurans resulted in increased expression of genes of the RDR regulon, probably because of enhanced expression of irrE caused by the transposon (Devigne et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two proteins, DdrO and IrrE, ensure the regulation of the RDR genes after DNA damage. DdrO is a negative transcriptional regulator that binds the RDRM sequence and represses the expression of the RDR genes [2325]. IrrE is a metalloprotease [26] that cleaves, and thus inactivates DdrO after irradiation, leading to the transcriptional induction of the genes of the RDR regulon [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…PprA is produced after ionizing radiation exposure by induction via PprI-dependent posttranslational modification to DdrO of the transcriptional regulator by proteolysis (24)(25)(26). PprA can bind to double-stranded DNA and inhibit its degradation by E. coli exonuclease III (14).…”
mentioning
confidence: 99%